2012
DOI: 10.1128/jcm.01292-12
|View full text |Cite
|
Sign up to set email alerts
|

Visual Detection ofrpoBMutations in Rifampin-Resistant Mycobacterium tuberculosis Strains by Use of an Asymmetrically Split Peroxidase DNAzyme

Abstract: dMultidrug-resistant Mycobacterium tuberculosis is resistant to two first-line antituberculosis drugs, isoniazid and rifampin, resulting in the relapse of tuberculosis. M. tuberculosis grows very slowly, and thus traditional examination methods take time to test its drug resistance and cannot meet clinical needs. The use of a DNA probe makes it possible to test rifampin resistance. We developed an asymmetrical split-assembly DNA peroxidase assay to detect drug-resistant mutation of rifampin-resistant M. tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…The occurrence of NI results where the wild type probes failed to hybridize to their corresponding sequences could result from the inaccessibility of the genomic sequence in a given sample, such as when secondary DNA structures are present. This problem has been noted in rpoB hybridization, in particular, and might play a role in the observed high occurrence (27.5%) of NI results proven RIF-susceptible in this study [36]. …”
Section: Discussionmentioning
confidence: 72%
“…The occurrence of NI results where the wild type probes failed to hybridize to their corresponding sequences could result from the inaccessibility of the genomic sequence in a given sample, such as when secondary DNA structures are present. This problem has been noted in rpoB hybridization, in particular, and might play a role in the observed high occurrence (27.5%) of NI results proven RIF-susceptible in this study [36]. …”
Section: Discussionmentioning
confidence: 72%
“…S1). It is reported that after asymmetric PCR, a Cy5 labeled ssDNAs in the PCR product of the MTB undergoes self-dimerization due to the complementary base pairs in its sequence [27]. Therefore, a splitter DNA was used to separate the strands of the Cy5 labeled ssDNA in the dimerized form.…”
Section: Mtb-dr-rif 9g Membrane Manufacture and Hybridizationmentioning
confidence: 99%
“…Hence, a number of studies resorted to splitting the unabridged G-rich strand into an asymmetric ratio instead [63,64]. In a system involving the asymmetrical split DNAzyme strategy to rapidly and visibly detect rifampin-resistant M.tb with mutations in the rpoB gene, unequal ratio (3:1) of probe A and probe B were assembled through hybridization with the target ssDNA [64]. Since the target DNA was originally in dsDNA form, asymmetric PCR was applied to produce ssDNA.…”
Section: G-quadruplex-based Detection Systemmentioning
confidence: 99%
“…The formed DNA G4 is then converted into a DNAzyme that will subsequently catalyze the H 2 O 2 -mediated oxidation of ABTS 2− through peroxidation-like activity when bound with hemin. As a result, an oxidation product, ABTS − was formed and a visible green color was observed [64].…”
Section: G-quadruplex-based Detection Systemmentioning
confidence: 99%